Ln[N(SiMe3)2]3‐Catalyzed Cross‐Diinsertion of CN/CC into an NH Bond: Facile Synthesis of 1, 2, 4‐Trisubstituted Imidazoles from Propargylamines and Nitriles. Issue 28 (11th June 2014) - Hong, Longcheng; Shao, Yinlin; Zhang, Lixin; Zhou, Xigeng
Abstract A lanthanide‐catalyzed sequential insertion of CN and CC into an NH bond is presented. The convenient reaction, which proceeds under mild conditions, is an efficient method for preparing 1, 2, 4‐trisubstituted imidazoles directly from readily available propargylamines and nitriles.